AMBIGUITAS PERLAWANAN PAJAK LEMBAGA PERKREDITAN DESA (STUDI FENOMENOLOGI PADA LEMBAGA PERKREDITAN DESA DI PROVINSI BALI) - I Gede Yudi Primanta; Made Sudarma; Aji Dedi Mulawarman (Jurnal Akuntansi Aktual, 2018)
The research aims to  understand businessmen’ tax awareness and tax resistance for their business in Lembaga Perkreditan Desa (LPD). The research applies qualitative methode with transcendental phenomenology. The results of the study shows that LPD is supposed to be discharged from the tax duty. LPD has a significant role in preserving the custom and culture of Bali. Besides,  some LPD businessmen are aware of their tax duty charged for running the LPD.